Kepuasan Pengguna Jasa Sarana Bantu Navigasi Pelayaran di Pelabuhan Tanjung Priok - Ilmiyawan Syaf Agus; David A. Lasse; Cokorda Bagus (Institut Transportasi dan Logistik Trisakti, 2020)
This study is to find out the effect of dependent and independent variables through intervening variable simultaniously, partially, directly and indirectly. The study was conducted in Navigation District of Tanjung Priok. The variables are Performance & Maintenance (independent variables), Supervision (intervening variable), & Users' Navigation Aids Service Satisfaction (dependent variable). There was 96 respondents as samples tested using simple random sampling. The hypothesis was using path analysis based on the previous data of correlation & regression analysis. The results are (1) in the 1st model structure, the Independent & Intervening Variables simultaniously positive and significant affect the Dependent Variables, (2) in the 2nd model structure, the Independent Variables simultaniously positive and significant affect the Dependent Variable, (3) partially, each of the Independent Variables indirectly positive and significant affect the Users' Service Satisfaction mediated by the Navigation Aids Supervision